PENGARUH SOCIAL NETWORKING, BIAYA KULIAH DAN PELAYANAN TERHADAP PENGAMBILAN KEPUTUSAN KULIAH DI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN MEDAN - Hajatina Hajatina (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2021)
The supporting elements that play an active role in all sectors include education. In improving the quality of education, educational institutions must maximize quality learning patterns in the face of developments in science and technology. This study concluded that there was a significant influence both partially and simultaneously between social networking variables (x1) of 0.013, tuition fees (x2) of 0.005 and services (x3) of 0.010 on new student admissions at the Faculty of Economics and Business with alpha 0,05%.